Analisis Dampak Lingkungan Praktek, Pengalaman, dan Tingkat Pendidikan Perawat dalam Mengambil Keputusan Triage di Instalasi Gawat Darurat Rumah Sakit Umum Pulau Lombok - Baiq Fitrihan Rukmana; Muhammad Amrullah; Erwin Wiksuarini; Hamdan Hariawan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Abstract : Triage is an important thing to do in emergency unit installation. It is used to determine priority of emergency management to allow medical team handling patients whom need quick management accurately and being capable of improving life opportunity of the patient. Triage begins since a patient enters emergency unit where its nurses assess based on subjective and objective reviews quickly and accurately. However, this process requires supportive knowledge, experience, education, and working environment in determining priority of the patients. This research aims to identify factors correlating to triage decision making of the nurses in Lombok Nusa Tenggara Barat emergency unit. It is an analytic observational research with cross sectional approach by taking 135 respondents. The findings showed correlation among knowledge, experience, education, and working environment to triage decision making with each p score is 0.000. The most influential variable is knowledge with coefficient B 5.204. Knowledge, experience, education, and working environment influenced triage decision making. It is also expected to have standard requirement for nurses working in triage room so triage may run maximally.